Early‐life telomere length predicts lifespan and lifetime reproductive success in a wild bird. Issue 5 (1st April 2019) - Eastwood, Justin R.; Hall, Michelle L.; Teunissen, Niki; Kingma, Sjouke A.; Hidalgo Aranzamendi, Nataly; Fan, Marie; Roast, Michael; Verhulst, Simon; Peters, Anne
Abstract: Poor conditions during early development can initiate trade‐offs that favour current survival at the expense of somatic maintenance and subsequently, future reproduction. However, the mechanisms that link early and late life‐history are largely unknown. Recently it has been suggested that telomeres, the nucleoprotein structures at the terminal end of chromosomes, could link early‐life conditions to lifespan and fitness. In wild purple‐crowned fairy‐wrens, we combined measurements of nestling telomere length (TL) with detailed life‐history data to investigate whether early‐life TL predicts fitness prospects. Our study differs from previous studies in the completeness of our fitness estimates in a highly philopatric population. The association between TL and survival was age‐dependent with early‐life TL having a positive effect on lifespan only among individuals that survived their first year. Early‐life TL was not associated with the probability or age of gaining a breeding position. Interestingly, early‐life TL was positively related to breeding duration, contribution to population growth and lifetime reproductive success because of their association with lifespan. Thus, early‐life TL, which reflects growth, accumulated early‐life stress and inherited TL, predicted fitness in birds that reached adulthood but not noticeably among fledglings. These findings suggest that a lack of investment in somatic maintenance during development particularly affects late life performance. This study demonstrates that factors in early‐life are related to fitness prospects through lifespan, and suggests that the study of telomeres may provide insight into the underlying physiological mechanisms linking early‐ and late‐life performance and trade‐offs across a lifetime.